"Братья меньшие" вчера и сегодня - Краснопевцев Валентин Павлович (Лениздат, 1991)
Экземпляры: ф.3 (1991) / Инвентарный номер: 34100 / Цена: / Сис.шифр: 28.68 / Авт.знак: К 78 / ГРНТИ: 34.33 / ББК: 28.688